Video Making Project To Improve Students‟ Autonomy And Ability In Transactional And Interpersonal Conversations - Arfiyantama, Riko ((JELE) Journal Of English Language and Education, 2015)
Speaking as one of the productive skills is considered difficult forforeign language learners. One of the efforts to solve the difficulty is improvingthe students‟ autonomy in speaking practice. The study is about the use ofvideo making to improve students‟ autonomy and speaking ability intransactional and interpersonal conversations. The objective of the study wasto find out how video making project is implemented in classroom. Students ofSMA 1 Limbangan were taken as the subject of the study. This study usedclassroom action research by conducting a pre-test, first cycle, and second cycleactivities particularly focused on speaking. The students‟ speaking achievementwas scored based on the video they had made. The students were also asked tofill the questionnaire to know their improvements in autonomy. The result ofthe research showed that the average score percentage of autonomy in pre-testwas 68%, cycle I result was 87% and cycle II result was 89%. While the resultalso showed that the average of students‟ speaking achievements in pre-test was60, cycle I was 68, and Cycle II was 73.It can be concluded that using VideoMaking project in teaching transactional and interpersonal conversations canimprove the students‟ speaking competence as well as autonomy.